Indigenous literature and resistance in Brazil: the protagonism of indigenous writer Eliane Potiguara - Guedes de Souza, Elis Regina (2024)
We know that the writer Eliane Potiguara is a voice of resistance in the midst of the erasure of the culture and literature of indigenous peoples, so this paper aims to highlight the role and contribution of this indigenous writer to Indigenous Literature by women in Brazil. Our study is a bibliographical survey of the writer's career, based on other indigenous voices that highlight her importance, as well as an analysis of some fragments of poems from her book Metade Cara, Metade Máscara (2018). As a theoretical contribution, we drew on Castro (2022), Graúna (2012), Mendonça (2012) and Mignolo (2017). We conclude our study by emphasizing that Eliane Potiguara, through her struggles and her writing, consolidates herself as the first indigenous woman writer in Brazil, inaugurating the indigenous women's writing movement in the country.